Family Support and Migration in Nigeria - Daniel Tuki (Africa Spectrum, 2025)
Using novel large-N survey data collected from the state of Edo – Nigeria's migration epicentre – this study examines how family support relates to people's migration aspirations and their perception of the risks associated with migrating to Europe. The regression results reveal that family support positively correlates with migration aspirations and raises people's confidence in their chances of reaching Europe should they decide to migrate, effectively decreasing their perception of migration risks. Women are less optimistic about reaching Europe than men. – – En s'appuyant sur des données d'enquête à grande échelle collectées dans l'État d'Edo, épicentre de la migration au Nigeria, cette étude analyse la relation entre le soutien familial, les aspirations migratoires des individus et leur perception des risques associés à la migration vers l'Europe. Les résultats des régressions montrent que le soutien familial est positivement corrélé aux aspirations migratoires et renforce la confiance des individus dans leurs chances d'atteindre l'Europe s'ils choisissent de migrer, réduisant ainsi leur perception des risques migratoires. Les femmes se montrent moins optimistes que les hommes quant à leurs chances d'atteindre l'Europe.
https://doi.org/10.7910/DVN/UGTPLM
Keywords: 300; Nigeria; migration aspirations; risk perception; family support; Europe; Edo State